ANALISIS PENGARUH KARAKTERISTIK PEKERJAAN, KEPUASAN KERJA, DAN KOMITMEN TERHADAP KINERJA KARYAWAN - Frismandiri, Dinda (Jurnal Ekonomi Modernisasi, 2007)
The objectives of this research are to analyze direct influence of job satisfaction to employee's performance, to analyze indirect influence of job satisfaction to employees performance through commitment, to analyze direct influence job characteristic to employees performance, and to analyze indirect influence of job characteristic to employees performance through commitment.Using questionnaire, data were collected from 111 employee’s overall BPR at Kota Malang, sample taken by Proportional Random Sampling. Analysis used Path Analysis to test the direct influence and indirectly between job satisfaction to performance, and direct influence and indirectly between job to performance thorugh commitment.Result of research indicates that the job satisfaction have the direct influence to performance and also have the indirect influence to performance through commitment. This finding support the research Morisson (1997), Alhassan (2002), Riza (2001), Bhuian and Menguc (2002), and Pantja Djati and M. Khusaini ( 2003). Job characteristic only have the indirect influence to employees performance that is through komitmen. This finding supporting the research of Chonko and Wood ( 1985) and Ramaswami, Agarwal And Bhargava (1993), but not supporting the research of Fried and Ferris (1987). This research shown that the best influence is direct job satisfaction to performance, its meaning most influencing variable of performance attainment is the make-up of job satisfaction